The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Campylobacter jejuni In Chicken Meat Marketed In Baghdad Province

Abstract: Campylobacter are the main cause of human bacterial intestinal disease identified worldwide. Over 90% of cases are caused by C. jejuni and about 5% of cases are caused by C. coli. Mishandling of raw chicken carcasses and consumption of undercooked chicken meat are the major risk factors for human campylobacteriosis. Despite the control measures for reducing cross contamination, the detection of Campylobacter in carcasses after chilling/freezing remains very high. The aim of this study was to determine the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Mezher et al [ 45 ] found that the occurrence of Campylobacter species in chicken meat samples were 6.80%, and 27.27% of isolates were identified as C. jejuni . The whole occurrence of C. jejuni amid the poultry meat samples collected from Iraq [ 46 ], Iran [ 47 ], Pakistan [ 48 ], India [ 49 ], Korea [ 50 ], and China [ 51 ] was 10%, 6.84%, 40%, 26.30%, 36.30%, and finally 1.82% to 56.00%, respectively. Boost occurrence of Campylobacter species was also conveyed in poultry meat samples collected from European countries (29%–41%) [ 52 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mezher et al [ 45 ] found that the occurrence of Campylobacter species in chicken meat samples were 6.80%, and 27.27% of isolates were identified as C. jejuni . The whole occurrence of C. jejuni amid the poultry meat samples collected from Iraq [ 46 ], Iran [ 47 ], Pakistan [ 48 ], India [ 49 ], Korea [ 50 ], and China [ 51 ] was 10%, 6.84%, 40%, 26.30%, 36.30%, and finally 1.82% to 56.00%, respectively. Boost occurrence of Campylobacter species was also conveyed in poultry meat samples collected from European countries (29%–41%) [ 52 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 20 C. jejuni strains (eight from cecal contents and 12 from frozen chicken carcass rinse) obtained from a previous study by Ghaffoori [25] were subjected to the biofilm detection method. Isolation and identification of these strains were performed according to the standard bacteriological protocols described by previous studies [25][26][27]. employing tests for oxidase, catalase, H 2 S generation, microaerobic growth, and hippurate hydrolysis in addition to microscopic analysis of morphology and motility.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Oxoid Biochemical Identification System Campy (Oxoid, ID0803M, United Kingdom) was used in further biochemical research to differentiate Campylobacter. The multiplex polymerase chain reaction assay was used to confirm the presence of C. jejuni strains, as previously reported by Ghaffoori [25].…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Much of the published research on Campylobacter in the Arab countries is centered around poultry (mainly chicken meat), followed by few studies in dairy products and other foods (Table 2). According to Ghaffoori [90], in Iraq, the prevalence of C. jejuni in broiler chicken carcasses (n = 20) was as high as 60%. In Saudi Arabia, Campylobacter Spp.…”
Section: Campylobacter In the Food Chain In The Arab Worldmentioning
confidence: 99%